A Mussoorie Mystery - Ruskin Bond (New Delhi, India Rupa & Co, 2017)
'Remember the old road, The steep stony path That took us up from Rajpur, Toiling and sweating And grumbling at the climb, But enjoying it all the same..' From 'Remember the Old Road' by Ruskin Bond Sometimes, a journey can be of discovery. And, in this compilation, Ruskin Bond has discovered hair-raising stories of other people's journeys, taken many many years ago. Bond describes the old track from Rajpur to Mussorie, surrounded by Oak trees and colonial buildings in 'The Kipling Road'. Braving blizzards and bandits, M. Huc takes a momentous journey to Ladakh in 'Journey to the Forbidden City', while Osa Johnson, the only woman adventurer in the book, gives her awe-inspiring account of cannibals in 'A Woman Among Cannibals'. Be it travelling for shikar or search for new lands or just for survival, this book is packed with action!
Keywords: Ruskin Bond -- Ruskin Bond